Valuing Access to Water--A Spatial Hedonic Approach, with an Application to Bangalore, India - Anselin, Luc; Lozano-Gracia, Nancy; Deichmann, Uwe; Lall, Somik (2012)
An important infrastructure policy issue for rapidly growing cities in developing countries is how to raise fiscal revenues to finance basic services in a fair and efficient manner. This requires estimates of the potential benefits or positive welfare effects that may follow from improved infrastructure. In this paper, we take advantage of a unique geo-referenced household survey to carry out a hedonic analysis of housing values that explicitly accounts for spatial spillovers. We use this to derive an estimate of the value of improved access to water in the Indian city of Bangalore. The findings suggest that by limiting the focus to individual or private benefits only, we may underestimate the overall social welfare from investing in service supply. We further demonstrate how spatially explicit policy simulations based on these estimates provide insight into the total effects of targeted interventions.